The Utilization of Waste Date Seed as Bio-Oil and Activated Carbon by Pyrolysis Process. (11th January 2012) - Joardder, Mohammad Uzzal Hossain; Uddin, Md. Shazib; Islam, Mohammad Nurul
Abstract : The renovation of biomass waste in the form of date seed waste into activated carbon and biofuel by fixed bed pyrolysis reactor has been focused in this study to obtain gaseous, liquid, and solid products. The date seed in particle form is pyrolysed in an externally heated fixed bed reactor with nitrogen as the carrier gas. The reactor is heated from 400 ° C to 600 ° C. A maximum liquid yield of 50 wt.% and char of 30 wt.% are obtained at a reactor bed temperature of 500 ° C with a running time of 120 minutes. The oil is found to possess favorable flash point and reasonable density and viscosity. The higher calorific value is found to be 28.636 MJ/kg which is significantly higher than other biomass derived. Decolonization of 85–97% is recorded for the textile effluent and 75–90% for the tannery effluent, in all cases decreasing with temperature increase. Good adsorption capacity of the prepared activated carbon in case of diluted textile and tannery effluent was found.